Estudos de asfaltenos e resinas por espectroscopia de RMN - Madeira, Natã Carlos Lira (2018)
One of the major problems encountered during the processing and extraction of petroleum is the deposition of asphaltenes, a phenomenon that causes several prejudicesuch as the clogging of oil welland damages onthe reservoir rock. The literature is divided on the assertion that the resins are able to decrease the formation of aggregates, due to their similarity in chemical structure with asphaltenes.However, thereare studies that claim that resins are not capable of acting as surfactants and the factor that limits the size of the aggregate would be the repulsioninteractionsamongtheasphaltenesthemselves. Due to this problem, this work was carried out to verifythe influence of resins on the size of the asphaltene aggregatesformed.For this estudy, were used Three petroleum samples of different origins and ºAPI, obtained in the national territory, were perfomed to extract asphaltenes from ASTM D6560-00. The extraction of resins occurred by chromatography from the adaptation of ASTM D2549. Afterwards, was perfomed the characterization of the samples by¹H and 1³C NMR techniques, thatallowed to verify the architecture of the asphaltenes presents and the content aromatic carbons, a result that deduces the amount of fused rings in the sample a factor that is related to the stability of the asphaltenes, due to the possibility of p-p stacking type interactions. Also, worse NMR of ¹H and ³³C it was possible to get an idea of the structure of the oils and resins.The influence of the resins on the size of the aggregates was determined using the DOSY technique, with experiments performed on deuterated toluene at a concentration of 5% (w/w) asphaltenesadding 5 mg of resins for three times, getting the masses of 5, 10 and 15 mg of resins in solution containing. With the relative diffusion values measured in the experiment it was possible to verify that the sample of smaller ºAPI had a greater aromatic character in the asphaltenes, having very little influence of the resins in the aggregate size,However, the samples of higher ºAPI had a significant influence on the size of the aggregates from the addition of 10 mg of resins, indicating the existence of this influence on the size of the aggregates, but observing that in order to have such influence, the necessary and compatible structural conditions of the resins with their respective asphaltenes